The relation between mortality salience, traffic locus of control, and risky driving behavior. Issue 2 (7th February 2021) - Măirean, Cornelia; Havârneanu, Corneliu-Eugen
Abstract: This study evaluated the direct relationships between mortality salience (MS), traffic locus of control (T-LOC), and risky driving behavior. The sample included 170 drivers. They completed scales measuring T-LOC, then they were randomly divided into one of the three condition groups: MS condition, traffic accidents MS condition, and the control condition. At the end, the participants completed a scale for measuring risky driving behavior. The results showed that MS interacts with the relevance of driving for self-esteem and with external T-LOC in determining risky driving. The implications of these results for safety and future research are discussed.